2013
DOI: 10.1021/ja409788k
|View full text |Cite
|
Sign up to set email alerts
|

Structure Prediction of Au44(SR)28: A Chiral Superatom Cluster

Abstract: The structure of a thiolate-protected Au44 cluster, [Au44(SR)28], is theoretically predicted via density functional theory calculations. Au44(SR)28 is predicted to contain a "two-shell" face-centered-cubic type of Au kernel and possess chirality. The predicted cluster structure is validated by comparison of optical absorption properties between theory and previous experiments, as well as energy evaluations. Based on the predicted cluster structure, the magic stability of Au44(SR)28 is understood from the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 50 publications
4
108
0
Order By: Relevance
“…The structures of atomically precise and highly fluorescent Au NCs have been extensively studied and various structures have been predicted corresponding to different number of atoms . It is accepted that the high stability of Au NCs is relevant to the electronic number fulfilling both the closed electron shell rule and geometric factors.…”
Section: Au Ncs: the Present Fundamental Understandingmentioning
confidence: 99%
“…The structures of atomically precise and highly fluorescent Au NCs have been extensively studied and various structures have been predicted corresponding to different number of atoms . It is accepted that the high stability of Au NCs is relevant to the electronic number fulfilling both the closed electron shell rule and geometric factors.…”
Section: Au Ncs: the Present Fundamental Understandingmentioning
confidence: 99%
“…have been successfully characterized experimentally. Besides the experimental crystallization, the structures of RS-AuNPs such as Au 20 (SR) 16 , 23 Au 24 (SR) 20 , 24 Au 38 (SR) 24 , 25 Au 44 (SR) 28 , 26 Au 68 (SR) 32 , 27 Au 144 (SR) 60 , 28 and etc. have been predicted theoretically.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14-21 Later, structures of a thiolate-protected gold clusters were predicted chiral via density functional theory calculations. [22][23][24][25][26][27][28] Potential applications of the chiral gold clusters in enantioselective and catalytic reactivity were also discussed therein. A recent study by Elgavi et al demonstrated that chirality could exist in copper nanoalloy clusters.…”
Section: Introductionmentioning
confidence: 99%